Hakai is required for stabilization of core components of the m6A mRNA methylation machinery - Praveen Bawankar (Nature Portfolio, 2021)
The E3 ligase Hakai can interact with the m6A methylation machinery but its function is still unclear. Here, the authors show that Hakai is a conserved component of the m6A methyltransferase complex and provide functional and molecular insights into its role in regulating m6A levels in Drosophila.